Analysis of putative sclerotia maturation-related gene expression in Rhizoctonia solani AG1-IA - Liu, Bo; Ma, Zhoujie; Gai, Xiaotong; Sun, Yanqiu; Wang, Yanfeng; He, Shidao; Gao, Zenggui (Archives of Biological Sciences, 2018)
Paper description: A cDNA library of Rhizoctonia solani AG1-IA, a major soil-borne fungal pathogen of maize, was constructed and qRT-PCR analysis was performed to determine the expression of twelve R. solani AG1-IA genes during three stages of sclerotial formation (mycelium, initiation of sclerotium and maturation of sclerotium). The results of our study provide new findings related to the methods of prevention and control of disease caused by R. solani AG1-IA. Abstract：Rhizoctonia solani AG1-IA (R. solani AG1-IA) is a major soil-borne fungal pathogen of maize that causes significant yield losses in all maize-growing regions worldwide. The sclerotium produced by R. solani AG1-IA can overwinter in grass roots or diseased plants and infect crops the following year. The molecular mechanism underlying sclerotium formation in R. solani is poorly understood. In this study, we constructed the cDNA library of the R. solani AG1-IA pathogenic strain WF-9, from which 329 high-quality expressed sequence tags (ESTs) were obtained. Of the 250 clustered unigenes, 12 genes were selected for further expression analysis during the three stages of sclerotial growth (mycelium, initiation of sclerotium, and maturation of sclerotium). The results of expression analysis support the previously suggested roles of chitin synthase D and exo-beta-1,3-glucanase in facilitating sclerotial growth through preservation of water content and energy. In addition, cytochrome P450, NADPH oxidase, catalase (CAT), acyl-CoA oxidase 1 (ACOX1), mitogen-activated protein kinase (MAPK), mitogen-activated protein kinase HOG1 (HOG 1), and the G-protein α subunit play important roles in balancing reactive oxygen species (ROS) levels during sclerotial development. The findings of this study can help understand the molecular mechanism of sclerotial development further. https://doi.org/10.2298/ABS180106026L Received: January 6, 2018; Revised: May 1, 2018; Accepted: May 4, 2018; Published online: Jun 14, 2018 How to cite this article: Liu B, Ma Z, Gai X, Sun Y, Wang Y, He S, Gao Z. Analysis of putative sclerotia maturation-related gene expression in Rhizoctonia solani AG1-IA. Arch Biol Sci. 2018;70(4):647-53.